Crises climatiques, ruptures politiques et transformations de l’action publique environnementale au Mali - Amadou Hamath Dia; Sylvia Becerra; Fabrice Gangneron (VertigO)
This paper analyzes the environmental policy process in Mali, in the context of the successive and severe drought since the seventies. Certainly, those climatic hazards have put on policy’s agenda the interdependences between natural resources degradation and social-economical dynamics (PNAE- PAN/CID, 1998). They also have permitted a best consciousness on environmental problem’s complexity. But, only they don’t explain all the changes which can be observed in the nineties in this field. We show that the political breacking-point in 1991 (democracy access, multipartismes, decentralization) opened a propitious policy-window (Kingdon, 1984) for developing a structured (legal actions and institutional frame) and concerted environmental policy in the country.